Profil Penggunaan Terapi Farmakologi dan Non Farmakologi pada Dismenore di SMAN 1 Meureudu Kabupaten Pidie Jaya - Amelia Sari; Irma Afna Mulya; Noni Zakiah; Burdah; Defri Aroni; Maria Irwani (Journal of Pharmacy and Clinical Practice, 2026)
Dysmenorrhea is a common menstrual pain experienced by adolescent girls and can negatively affect quality of life, learning activities, and daily productivity. The high prevalence of dysmenorrhea among adolescents, along with variations in the choice of treatment—both pharmacological and non-pharmacological—highlights the importance of understanding the patterns of therapy use that are safe and effective. This study aimed to describe the use of dysmenorrhea treatment among female students at SMAN 1 Meureudu, Pidie Jaya Regency. This study employed a descriptive design with a sample of 74 respondents selected through purposive sampling. The inclusion criteria were female students who had used pharmacological and/or non-pharmacological therapies and were willing to participate. Data were collected using a questionnaire and analyzed using univariate analysis. The results showed that the majority of respondents used non-pharmacological therapy (54.1%), followed by combination therapy (41.8%), and pharmacological therapy (4.1%). The most commonly used pharmacological treatment was paracetamol (40.3%), while the most frequently used non-pharmacological method was warm compress (23.8%). These findings indicate that adolescents tend to prefer non-pharmacological approaches in managing dysmenorrhea. Therefore, appropriate education is needed to ensure the selection of effective and rational treatment methods. Keywords: adolescent dysmenorrhea, pharmacological therapy, non-pharmacological therapy, paracetamol, warm compress